Effects of Repetitive Transcranial Magnetic Stimulation on Tumor Necrosis Factor Alpha in Neuropsychological Disorders: A Systematic Review and Meta‐Analysis - Arya Asadizeidabadi; Seyedmohammadamin Hosseini; Artem Pyatkov (Brain and Behavior, 2025)
ABSTRACT Introduction: Repetitive transcranial magnetic stimulation (rTMS) shows promise in treating neuropsychological disorders. This systematic review and meta‐analysis investigated the effects of rTMS on inflammatory cytokines and brain‐derived neurotrophic factor (BDNF) under these conditions. Method: We searched five electronic databases for relevant studies. Twelve studies (six randomized controlled trials [RCTs] and six cohort studies) were included in the systematic review, with six RCTs included in the meta‐analysis. The primary outcome was tumor necrosis factor‐alpha (TNF‐α) levels, with secondary outcomes including interleukin‐6 (IL‐6), interleukin‐1 beta (IL‐1β), high‐sensitivity C‐reactive protein (hs‐CRP), interferon‐gamma (IFN‐γ), and BDNF. Results: Meta‐analysis revealed a significant decrease in TNF‐α levels after rTMS (weighted mean difference [WMD]: −6.65, 95% confidence interval [CI]: −10.47–2.83, p < 0.05), with greater effects associated with longer interventions. No significant change was found in the IL‐6 levels. BDNF levels increased significantly (WMD: 7.97, 95% CI: 2.8–13.15, p < 0.05). Qualitative synthesis indicated consistent reductions in IL‐1β. High heterogeneity was observed in some analyses. Conclusion: rTMS may exert therapeutic effects on neuropsychological disorders partly through modulating neuroinflammation and promoting neuroplasticity. However, high heterogeneity and study limitations necessitate larger, more standardized clinical trials to confirm these effects and explore their clinical significance.